MENINGKATKAN SIKAP EMPATI MELALUI METODE MENDONGENG PADA ANAK USIA DINI - Wiwin Winangsih; Lastri Yuniarti; Ema Aprianti (IKIP Siliwangi, 2018)
Empathy is the ability of someone to put themselves in the position of others, to understand the views and feelings of people or to experience what the person experienced. Storytelling method is a way of delivering the learning done orally and by engineered by the storyteller of movement and body expression, the fairy tale has a specific meaning that is something related to the world of fantasy.the empathy ability of children of A group Bustanul Arifin Kindergarten is still low. The purpose of this study is to obtain an overview of the improvement of empathy ability of children through the application of storytelling method. The research was done by research method of class action of this research data collected through observation and documentation of data which have been collected analyzed by description.In accordance with the results of the research we have analyzed and it can be concluded that the development of empathy of Group A children from the number of children 25 consisting of 12 males and 13 girls in fact has increased, this is derived from the final result after the implementation of the action on cycle 2 which can be explained from each number of children in the category of BB as many as 3 children, in the MB category, as many as 7 children, in the category of BSH, as many as 11 children, and on BB category, a number of 4 children.